INALL exchange visit between Senegal, Burkina Faso and Tunisia - sib, ollo; Piraux, Marc; Rudiger, Udo; Gueye Fall, Modou; Sene, Mame Birame; Vall, Eric (2025)
The report describes objectives and different elements of the INALL exchange visit with participants of three countries.